2015
DOI: 10.1021/acs.jpcb.5b08845
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Shocked Formic Acid: Born–Oppenheimer MD Calculations of the Shock Hugoniot and Early-Stage Chemistry

Abstract: Quantum and classical molecular dynamics simulations are used to explore whether chemical reactivity of shocked formic acid occurs at pressures greater than 15 GPa, a question arising from results of different shock compression experiments. The classical molecular dynamics simulations were performed using a quantum-based nonreactive pair additive interaction potential whereas the full resolution quantum mechanical molecular dynamics simulations allow chemical reactions. Although the shock Hugoniot curve calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In particular, the hydrogen atom dissociation and intramolecular transfer can lead to the formation of new intermediates, such as HONO, which trigger alternative initiation pathways for RDX and HMX decomposition. Rice and Byrd et al performed QM-MD simulations of PETN and formic acid under shock conditions, where they observed the excessive mobility of atomic hydrogen migrating between decomposing molecules and clusters. This mobility was especially pronounced in their shock simulations, where hydrogen atoms were propelled forward ahead of the mass flow at the shock front.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the hydrogen atom dissociation and intramolecular transfer can lead to the formation of new intermediates, such as HONO, which trigger alternative initiation pathways for RDX and HMX decomposition. Rice and Byrd et al performed QM-MD simulations of PETN and formic acid under shock conditions, where they observed the excessive mobility of atomic hydrogen migrating between decomposing molecules and clusters. This mobility was especially pronounced in their shock simulations, where hydrogen atoms were propelled forward ahead of the mass flow at the shock front.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, using ab initio QMD this time, Chang et al found 75 different species, many short-lived, and over 100 reactions for the decomposition of solid phase NM, further illustrating the complex chemistry of the compound. Even studies on formic acid HCOOH, a simpler compound that is observed during the decomposition of NM (Figure ), show an “extensive and complex chemical reaction” (Rice and Byrd, also using ab initio QMD) with numerous intermediates and intermolecular complexation leading to the appearance of large compounds that would most likely be omitted in detailed kinetics models (see for instance Figures 5, 7, and 8 in ref ).…”
Section: Resultsmentioning
confidence: 99%